The movement evaluation of Gourband fault according to morphotectonic and new neotectonic evidences (eastern south of Torbat e Jam) - Mohsen Jami; Mohamadmahdi Khatib; Ali Asqar Moridi Farimani; s.hosein mirzeinalei yazdei (جغرافیا و توسعه, 2015)
The under study area  is  located at the north east of Iran at  the vicinity of  Torbat e jam city. The main faults like Golbano, Gourband, Jahan-Abad, Rasoul-Abad and Kajab are located at a short  distances from Torbat e jam city. Gourband fault is the largest fault in alluvial sediments of Torbat e jam plain that has north west – south east trend. Studying the geotectonical activity of the mentioned fault regarding its proximity to the city and locating various villages in its neighboring has  a great  importance. In this research, the effect of recent movements of this fault on the structural geomorphology of the region has been studied. To evaluate geotectonic actions of the studied fault, morphotectonic (Smf, V, SL) has been used as the main tool. Studying neotectonic morphology indices indicate high activity of this fault. The existence of fault rises, changing route of streams and channels, ‘V’ shape valleys, folds of quaternary sediments and change of color in sediments at the fault zone are  of the important geomorphologic indices that is observed in field surveying and in connection with the movement of Gourband fault. The movement in channels indicates the youngest movement along this fault, the direction of these channels also indicates the  right direction of slip movement in the mentioned fault. The existences of rise in neogen sediments  at the  location of superficial effect of fault also indicate rising and reserved component in this fault.